Vocational learning : innovative theory and practice - Catts, Ralph [Herausgeber]; Falk, Ian [Herausgeber]; Wallace, Ruth [Herausgeber] (Springer, 2011)
"Effective knowing and learning for vocational purposes must take account of the wide range of variables that impact on knowledge formation and therefore promote learning. In light of those many variables, the formal system sector of vocational learning must constantly ask itself what could and should be done to better provide vocational learning for those people likely to pursue learning via the informal sector. This book addresses that question. Vocational Learning: Innovative Theory and Practice discusses four theoretical aspects of vocational learning that support understanding of vocational learning processes and practices: the situatedness of vocational learning; the power and roles of social networks and identity in vocational learning; knowing and knowledge management processes; and the implications for pedagogic practices in both informal and formal TVET systems. The book provides an overview of a series of international examples of innovative approaches to vocational educational theory and practice, and it draws on empirical research to analyze the effects of those approaches. It includes unique insights into aspects of TVET for Indigenous Peoples. With a discussion of policy implications for Europe, North America and Australia, this book is an instrumental tool to understand the underlying factors that generate effective educational and workforce outcomes through effective formal and informal learning." (Publisher, BIBB-Doku)
Keywords: L 2.2 Didaktik; T 2.2 Lerntheorien; L 2.3 Methoden; Berufsbildung; Didaktik; Lerntheorie; Lernmethode; Bildungspersonal; Internationaler Vergleich